Jual Beli Pakaian Bekas Impor dalam Tinjauan Fikih Muamalah dan Permendag No. 40 Tahun 2022 (Studi Kasus di Pasar Senggol Kota Parepare) - Ashar Ashar; Ronny Mahmuddin; Azwar Azwar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the practice of buying and selling imported used clothing at Senggol Market, Parepare City in a review of Muamalah Fiqh and Permendag Number 40 of 2022. This research uses qualitative methods in the form of field research with normative juridical, empirical juridical, and sociological approaches . The results of the study show that: first, the practice of buying and selling imported used clothing at Senggol Market, Parepare City involves three parties, namely distributors, sellers, and buyers. The seller orders and buys imported clothes from the distributor in the form of sacks and then resells them on the market in units to the buyer. Second, when viewed from the contract between the seller and the buyer, the practice of buying and selling imported used clothing at Senggol Market, Parepare City, is generally appropriate and fulfills the provisions of the pillars and conditions of sale and purchase according to fiqh muamalah. Meanwhile, if viewed from the contract between the seller and the distributor using the wholesale system, the practice of buying and selling imported used clothing at Senggol Market in Parepare City contains elements of garar (unclearness), but is included in the category of garar yasīr (light garar) which is permissible and does not damage the validity of the contract. Third, imported used clothes are goods that are prohibited from being imported into Indonesian customs territory in the perspective of positive law as regulated because they are deemed to be harmful to society and the domestic industrial market.